Jembatan Jarak Jauh: Pengaruh Komunikasi Interpersonal terhadap Intimacy Pasangan LDM melalui Love Language : Penelitian - Fatya Maulidina; Raras Sutatminingsih; Rahma Fauzia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines the influence of interpersonal communication on intimacy in individuals undergoing long-distance marriages (LDM) with love language as a mediating variable. The method used was a quantitative correlational study with 233 participants. The research instruments included the Interpersonal Communication Inventory (ICI), Personal Assessment of Intimacy in Relationships (PAIR), and the Five Love Language Scale modified to suit the LDM context. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping through SmartPLS. The results indicated that interpersonal communication had a very significant effect on intimacy with an R² of 0.972. All aspects of love language significantly mediated the relationship (t-statistic > 1.96; p < 0.05). Physical Touch was the most dominant mediator (original sample value 0.364), followed by Words of Affirmation (0.202), Quality Time (0.195), Receiving Gifts (0.129), and Acts of Service (0.057). These findings emphasize the importance of effective interpersonal communication and the application of love languages in maintaining intimacy in long-distance couples. Theoretical and practical implications are discussed in the context of marriage counseling and psychological interventions.